Pengaruh Komunikasi Digital Dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Organizational Citizenship Behavior Sebagai Variabel Mediasi Pada PT. Erlimaem Lestari Abadi - Rohan Firmansah; Ramdani Bayu Putra; Mardhatilla Fitri Sopali (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study examines the role of digital communication and work discipline in influencing employee performance, with Organizational Citizenship Behavior (OCB) as a mediating variable at PT. Erlimaem Lestari Abadi. The study aims to analyze the direct effects of digital communication and work discipline on employee performance and to investigate whether OCB mediates these relationships. A quantitative approach was employed using a survey method. The population consisted of all company drivers, totaling 51 respondents, selected through a saturated sampling technique. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that digital communication has a positive and significant effect on OCB, whereas work discipline does not significantly influence OCB. Furthermore, digital communication, work discipline, and OCB do not have a significant direct effect on employee performance, and OCB does not function as a mediating variable. These results indicate that digital communication plays a greater role in encouraging employees’ voluntary organizational behaviors rather than directly improving performance outcomes. This study contributes practical implications for human resource management, particularly in strengthening organizational behavior in the transportation sector.